Incorrectly corrected? QT interval analysis in rats and mice - Mulla, Wesam; Murninkas, Michael; Levi, Or; Etzion, Yoram (Frontiers in Physiology, 2022)
QT interval, a surrogate measure for ventricular action potential duration (APD) in the surface ECG, is widely used to identify cardiac abnormalities and drug safety. In humans, cardiac APD and QT interval are prominently affected by heart rate (HR), leading to widely accepted formulas to correct the QT interval for HR changes (QT corrected - QTc). While QTc is widely used in the clinic, the proper way to correct the QT interval in small mammals such as rats and mice is not clear. Over the years, empiric correction formulas were developed for rats and mice, which are widely used in the literature. Recent experimental findings obtained from pharmacological and direct pacing experiments in unanesthetized rodents show that the rate-adaptation properties are markedly different from those in humans and the use of existing QTc formulae can lead to major errors in data interpretation. In the present review, these experimental findings are summarized and discussed.